Hollywood and Hitler : 1933 - 1939 - Doherty, Thomas Patrick, 1952- 1952- (Film and culture, 2013)
The abundance of WWII-era documentaries and the huge cache of archival footage that has emerged since 1945 make it seem as if cinematic images of the Nazis were always as vivid and plentiful as they are today. Yet between 1933 and 1939, representations of the Nazis and the full meaning of Nazism came slowly to Hollywood, growing more distinct and ominous only as the decade wore on. Recapturing what ordinary Americans saw on the screen during the emerging Nazi threat, Thomas Doherty reclaims forgotten films, such as 'Hitler's Reign of Terror' (1934), a pioneering anti-Nazi docu-drama by Cornelius Vanderbilt, Jr.; 'I Was a Captive of Nazi Germany' (1936), a sensational true tale of 'a Hollywood girl in Naziland!'; and 'Professor Mamlock' (1938), an anti-Nazi film made by German refugees living in the Soviet Union. Doherty also recounts how the disproportionately Jewish backgrounds of the executives of the studios and the workers on the payroll shaded reactions to what was never simply a business decision